Keterterapan Prinsip-Prinsip Pengendalian Internal dalam Tata Kelola Badan Usaha Milik Desa (BUM Desa) di Kabupaten Sidoarjo - Linda Oktaviani; Dian Anita Nuswantara (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2020)
This research discuss the level of internal control principles applicability at Village-Owned Enterprises (VOE) in Sidoarjo. Descriptive qualitative approach with Participatory Action Research (PAR) is employed to develop an appropriate internal control framework for VOE in Sidoarjo. The data are primary data from primary sources, they are a VOE Chairman and a VOE’s employee from three VOE. Data collected through interviews and documentation. Then, technique and source triangulation was carried out to test the data validity. The results showed that the magnitude’s level of internal control was still low. While the COSO internal control principles can be applied by VOE with modifications.